Pre-Match Anxiety Levels in Pencak Silat Athletes - Gani, M Abdul; Bukman Lian; Sugarwanto (Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2024)
Studi Purpose The problem in this study is that the level of anxiety of PSHT pencak silat athletes in Sumber Jaya Village has not been dictated in facing the match. This study aims to determine the level of anxiety of PSHT pencak silat athletes in Sumber Jaya Village in Facing Matches. Method in this study uses quantitative descriptive. The study population was 15 people, while the sample used the total population. Data collection was done using a likert scale questionnaire. Data analysis uses a percentage description. Result of this study is that the level of anxiety of PSHT Pencak Silat athletes in Sumber Jaya Village in facing matches is 83.47%, this is that the anxiety of facing athletes' matches in imitating their athletes to practice is high.